The Urgency of Counselor Ethics in Providing Services to Counselees - Sari, Mustika (Jurnal Bimbingan dan Konseling Terapan, 2023)
This study aims to determine the important role of ethical values for a counsellor in providing services to counselees. The research method used is literature study or literature review. Literature review research is a series of activities related to library data collection methods reading and recording and processing research data, there are twenty articles/scientific works reviewed in this article regarding counsellor ethics. Based on the results of the study  or literature review that has been conducted, one of the values that must be possessed by a counsellor to build effective interactions between counsellors and clients is ethical values. Counselors in doing their work are proctected by a counselor’s code of ethics which  functions as a limitation, and work rules for counselors /counseling teachers. The counselor’s code of ethics is a moral foundation and professional behaviour guidelines that must be upheld and implemented by every member of the guidance and counseling profession in Indonesia. The code of ethics is prepared to serve as a guideline or guide counselors in doing their work so that guidance and counseling services run optimally.